Educational Technology Integration Strategies in Colleges of Teacher Education in Ethiopia - Misganaw Tadesse Woldemariam; Amanuel Ayde Ergado; Worku Jimma (Canadian Journal of Learning and Technology)
Research on educational technology (EdTech) integration has extensively explored determinants; however, strategies remain underexamined. Existing models predominantly focus on identifying the determinants of technology adoption yet fail to offer systemic frameworks for sustainable EdTech integration. This study bridges that gap by investigating strategies proposed by stakeholders in a college of teacher education, culminating in a theoretical framework. The research was conducted across four Ethiopian colleges of teacher education by employing a constructivist grounded theory. Data were collected through semi-structured interviews and document analysis, involving 23 participants selected through purposive and theoretical sampling. Data analysis was performed using MAXQDA (Version 2020) software. The results revealed six key strategies categorized into teacher-related, institution-related, and organization-related. A co-constructed theoretical framework illustrates the roles of various stakeholders in EdTech integration, underpinned by ecological systems theory, diffusion of innovations, and the unified theory of acceptance and use of technology. Credibility was ensured through a member-checking survey. The study advocates for further quantitative research to evaluate the correlation between strategies and educational technology integration outcomes, with replication across diverse contexts and stakeholders.